Fatigue Berhubungan dengan Kualitas Hidup pada Pasien Gagal Jantung - Rissa Latifardani; Dian Hudiyawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between fatigue and quality of life in heart failure patients. This study uses a correlative descriptive method utilizing a cross-sectional approach. Based on the study's results, most respondents were in the age range of 56-65 years with 39.6% and male sex as much as 61.3%. Most respondents are in the category of severe fatigue 77.4% and poor quality of life as much as 70.8%. Data analysis used the Chi-Square test, which produced a p-value of 0.001. In conclusion, a relationship exists between fatigue and quality of life in heart failure patients. Keywords: Heart Failure, Fatigue, Quality of Life